Association between thyroid function and diabetes peripheral neuropathy in euthyroid type 2 diabetes mellitus patients - He, Qingyuan; Zeng, Zekun; Zhao, Man; Ruan, Banjun; Chen, Pu (Scientific reports, 2023)
Previous studies disclosed that a high thyroid stimulating hormone level is an independent risk factor for diabetes peripheral neuropathy (DPN) in subclinical hypothyroidism (SCH) patients with type 2 diabetes mellitus (T2DM). However, whether thyroid metabolism has an effect on DPN in euthyroid T2DM patients remains unknown. The aim of this study was to identify the association between thyroid function and DPN in euthyroid T2DM patients. A set of 580 euthyroid T2DM patients was enrolled in the current study and stratified into DPN and Non-DPN groups. Mann–Whitney U test was performed to analyze the continuous variables of biochemical and thyroid metabolism indicators, and the Chi-square test was used to compare the categorical variables. Spearman correlation analysis was performed to analyze the relationship between clinical indicators and free thyroxine (FT4). By using the logistic regression analysis, the prevalence of DPN in different thyroid function indicators were evaluated. T2DM patients with DPN had obviously lower levels of aspartate aminotransferase (AST), alpha-hydroxybutyric dehydrogenase (α-HBDH), superoxide dismutase (SOD), calcium (Ca), creatinine (Cr), uric acid (UA), retinol binding protein (RBP), total protein (TP), albumin (ALB), alanine aminotransferase (ALT) and FT4 than the T2DM patients without DPN ( P < 0.05). FT4 was associated with TP, prealbumin (PA), ALB, SOD, anion gap (AG), Ca, chlorine (Cl), UA, RBP, apoprotein A (Apo A), apoprotein B (Apo B), apoprotein E (Apo E), and total cholesterol (TC). According to the FT4 quartile, participants were sequentially divided into four groups to compare the prevalence of DPN between each group. The data suggested that the prevalence of DPN in these four groups was 53.79%, 53.28%, 54.97%, 38.10%, respectively. Moreover, compared with quartile 4, patients in quartile 1, 2, 3 all had a significantly higher risk of DPN ( P = 0.007, P = 0.011, P = 0.004). The level of FT4 was negatively correlated with the prevalence of DPN in euthyroid T2DM patients.